2013
DOI: 10.1063/1.4818962
|View full text |Cite
|
Sign up to set email alerts
|

Strain evolution in GaN nanowires: From free-surface objects to coalesced templates

Abstract: Top-down fabricated GaN nanowires, 250 nm in diameter and with various heights, have been used to experimentally determine the evolution of strain along the vertical direction of 1-dimensional objects. X-ray diffraction and photoluminescence techniques have been used to obtain the strain profile inside the nanowires from their base to their top facet for both initial compressive and tensile strains. The relaxation behaviors derived from optical and structural characterizations perfectly match the numerical res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 64 publications
5
58
0
Order By: Relevance
“…1,24 Strain distribution simulations revealed that the decrease in the GaN nanorod diameter limits the strain relaxation depth to the surface, which can be extended along the entire nanorod length (strain still present at the base) by increasing its height up to $300 nm. 25,26 We adopted these conrmed dimensions to produce nano-LEDs using a combination of nanosphere lithography (NSL) and reactive ion etching (RIE). 27 The NSL/RIE procedure has been proven to result in noncoalesced, tightly size-controlled nanorods in contrast to the self-assembled Ni particle mask and selfor catalyst-induced epitaxial growth methods, 4,11,12,26 and to be faster, far less equipment demanding than the electron beam lithography and the focused ion beam patterning approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,24 Strain distribution simulations revealed that the decrease in the GaN nanorod diameter limits the strain relaxation depth to the surface, which can be extended along the entire nanorod length (strain still present at the base) by increasing its height up to $300 nm. 25,26 We adopted these conrmed dimensions to produce nano-LEDs using a combination of nanosphere lithography (NSL) and reactive ion etching (RIE). 27 The NSL/RIE procedure has been proven to result in noncoalesced, tightly size-controlled nanorods in contrast to the self-assembled Ni particle mask and selfor catalyst-induced epitaxial growth methods, 4,11,12,26 and to be faster, far less equipment demanding than the electron beam lithography and the focused ion beam patterning approaches.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 We adopted these conrmed dimensions to produce nano-LEDs using a combination of nanosphere lithography (NSL) and reactive ion etching (RIE). 27 The NSL/RIE procedure has been proven to result in noncoalesced, tightly size-controlled nanorods in contrast to the self-assembled Ni particle mask and selfor catalyst-induced epitaxial growth methods, 4,11,12,26 and to be faster, far less equipment demanding than the electron beam lithography and the focused ion beam patterning approaches. 1,14,28 Despite the fact that the nano-objects in this work were optically excited and not electrically pumped by means of contacts, they will still be termed nano-LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation profiles of ε || (z) and ε ||| (z) along the NW's growth axis are defined assuming exponential deformation decay [3,4,8,9]:…”
Section: Resultsmentioning
confidence: 99%
“…In [2], the assessment of macro-and micro-deformation in GaN NWs grown on Si(111) was performed with X-ray diffraction, where the NWs were found to be free of deformations on the macro scale but not on the micro scale. In comparison to self-assembled GaN NWs [2], an exponential relaxation of the macro-strain along the NW height was observed for top-down fabricated GaN NWs grown on silicon and sapphire substrates [3,4]. An exponential decay of the mean-squared micro-strain along the self-assembled GaN NW was considered to describe the X-ray diffraction peaks in [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation